Generation Z's Reception of Horror Messages and Gender Myths in the Petaka Gunung Gede Movie - Najwa Salsabilah; Mirza Azkia Muhammad Adiba (International Journal of Social Sciences and Humanities, 2026)
This study analyses Generation Z's reception of the Indonesian horror film Petaka Gunung Gede using Stuart Hall's decoding theory. The film is based on a true story that went viral on YouTube with 17.1 million views and raises local myths of Mount Gede, including the prohibition for menstruating women to climb and the sacredness of Alun-Alun Suryakencana. A qualitative approach was employed using in-depth interviews and a focus group discussion involving ten Generation Z informants (seven females and three males). The results reveal three decoding positions. The dominant-hegemonic position, held by 20% of informants, fully accepts the myths and prohibitions. The negotiated position, held by 60% of informants, accepts the moral message about respecting nature but remains skeptical toward mystical elements. The oppositional position, held by 20% of informants, rejects the myth as discriminatory against women. All oppositional informants are women, while all dominant informants are men. Despite differing decoding positions, almost all informants agree that the film successfully conveys the importance of maintaining ethics and respect for nature.